The Concept and Implementation of Contracts in Sharia Insurance Products: A Study at PT Asuransi Jiwa Syariah Bumiputera Serang - Fitriah Fitriah; Lailatul Uyun (Universitas Mercu Buana, 2026)
Abstract – This study aims to analyze the conformity between the concept and implementation of contracts in sharia insurance products at PT Asuransi Jiwa Syariah Bumiputera, located at the AJB Bumiputera Building, 2nd Floor, Jalan Veteran No. 11, Serang, Banten, with a focus on the application of tabarru’ and wakalah bil ujrah contracts in individual life insurance, group life insurance, and bancassurance products in accordance with sharia principles and DSN-MUI fatwas. The novelty of this study lies in its examination of various individual life insurance products such as Mitra Iqra Plus, Mitra BP Link Syariah, Mitra Mabrur Plus, and AJSB Assalam Family; group life insurance products such as Mitra Ekawarsa, Mitra Personal Accident Protection, and Mitra Ta’awun Fixed-Benefit Financing; as well as bancassurance products developed in collaboration with Islamic banks. This research employs a descriptive qualitative approach using interview and observation techniques. The findings indicate that, conceptually, all products have implemented contracts in accordance with sharia principles, including the separation of participants’ funds and company funds; however, gaps remain between the provisions stated in the policy documents and actual practices, particularly concerning the management of underwriting surplus and the transparency of ujrah.Keywords: Sharia Insurance; Tabarru’ Contract; wakalah Bil Ujrah; Mudharabah; Surplus Underwriting